Experimental investigation on the correlation between critical storage of elastic strain energy and crack extension in elastic–plastic materials. Issue 3 (13th December 2022) - Chang, Dongdong; Yang, Xiaofa; Liu, Ran; Huang, Zekai; Peng, Hao; Zuo, Hong
Abstract: To better solve the issues of steady crack extension with broad plasticity and the crack‐related problems in general yielding situations when the assumption of small‐scale plastic yielding fails, it is of great significance to further study the macroscopic mechanism of crack extension. In this paper, a new insight into the elastic–plastic crack extension is proposed on the foundation of critical storage of elastic strain energy (SESE). The feasibility of the new methodology is validated by designing and implementing two different experimental schemes in three typical elastic–plastic materials. The experimental results indicate that the critical SESE decreases linearly with the increase of crack length and U‐notch initial length. Besides, the SESE release rate is obtained through experimental and theoretical methods, and they are in the same order of magnitude and their value sequences are also accordant with all tested materials. Therefore, this investigation provides a new approach to characterizing crack extension in elastic–plastic materials. Highlights: A new insight is proposed to characterize crack growth in elastic–plastic materials. A novel experimental methodology is adopted to obtain the critical SESE. The established linear correlation is well validated by two experimental schemes. By experimental and theoretical methods, G is obtained and they fit each other well.